1990
DOI: 10.1177/1045389x9000100405
|View full text |Cite
|
Sign up to set email alerts
|

Aseismic Hybrid Control System for Building Structures under Strong Earthquake

Abstract: Two aseismic hybrid control systems recently proposed for protecting tall buildings against strong earthquakes are investigated and evaluated. The hybrid control system consists of a base isolation system connected to either a passive or active mass damper. The base isolation system, such as elastomeric bearings, is used to decouple the horizontal ground motions from the building, whereas the mass damper, either active or passive, is used to protect the safety and integrity of the base isolation system. The pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

1992
1992
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Here, k l varies with the lateral displacement, because G is strain dependent. The stiffness at a given displacement can be calculated from equation (1), provided the value of G used is for the appropriate rubber shear strain. In the region of the typical design rubber shear strain (100 per cent), the modulus does not vary strongly, and thus the isolators will show an approximately linear behaviour.…”
Section: Base-isolation Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, k l varies with the lateral displacement, because G is strain dependent. The stiffness at a given displacement can be calculated from equation (1), provided the value of G used is for the appropriate rubber shear strain. In the region of the typical design rubber shear strain (100 per cent), the modulus does not vary strongly, and thus the isolators will show an approximately linear behaviour.…”
Section: Base-isolation Systemmentioning
confidence: 99%
“…Isolation of buildings from the horizontal component of seismic ground motions is becoming more recognized as a method of protection. The horizontal components of earthquake ground motions are usually the most damaging to structures [1]. Referring to non-structural elements, the interstorey drifts and oor accelerations are the main sources of damage.…”
Section: Introductionmentioning
confidence: 99%
“…Recognizing that supplemental damping can effectively reduce seismic demands in BISs, 5,13 several researchers investigated the use of passive dynamic vibration absorbers for the task. Specifically, Yang et al 14 and Tsai 15 showed numerically that conventional tuned mass dampers (TMDs) comprising an oscillating secondary mass attached to the isolation layer via a viscoelastic link (ie, linear spring/stiffener in parallel with a linear viscous damper) can reduce seismic drift demands in base isolated multistorey buildings. Further, Taniguchi et al 16 considered the response of TMD-equipped BISs modelled as linear single degree of freedom (SDOF) systems exposed to several recorded GMs and showed that TMDs can reduce peak BIS displacement and, for some of the GMs, peak BIS acceleration as well.…”
Section: Introductionmentioning
confidence: 99%
“…Recognizing that supplemental damping can effectively reduce seismic demands in BISs, 5,13 several researchers investigated the use of passive dynamic vibration absorbers for the task. Specifically, Yang et al 14 . and Tsai 15 showed numerically that conventional tuned mass dampers (TMDs) comprising an oscillating secondary mass attached to the isolation layer via a viscoelastic link (ie, linear spring/stiffener in parallel with a linear viscous damper) can reduce seismic drift demands in base isolated multistorey buildings.…”
Section: Introductionmentioning
confidence: 99%
“…Some of the most common composites used as reinforcements have been glass fibre reinforced plastics (GFRP), carbon fibre reinforced plastics (CFRP) and basalt fibre reinforced plastics (BFRP). H. Yang et al [3] studied the flexural behavior of FRP reinforced glulam, they observed that reinforced poplar glulam with FRP increased the ultimate load by 18-63%, and bending stiffness by 32-88%. S. Li et al [4], L. Cheng et al [5] used CFRP and GFRP to reinforce LVL.…”
Section: Introductionmentioning
confidence: 99%